Millennial generation: An allusion to the specifics of employee retention in the consulting industry in Portugal - Bernardino, Inês Leal (2022)
Nowadays, the Portuguese workforce is composed of four generations, which causes challenges in Human Resources Management in terms of attracting, managing and retaining employees since younger generations´ (Generation Y and Z) interests, motivations and needs should coexist with the ones from past generations (Generation X and Baby Boomers). And, it becomes more challenging in the consulting industry because it is an industry that is characterized by having high turnover rates and low employee retention. Therefore, combining these industry characteristics and the Generation Y tendency to change jobs, makes it double challenging for managers to improve employee retention of the Millennial Generation. So, this study focuses on an allusion to the Generation Y´s specifics of employee retention in the consulting industry in Portugal, allowing to draw some conclusions on which factors contribute to Millennials´ job satisfaction and influence their decision to change jobs. Furthermore, based on prior literature research, this dissertation analyzes data collected through a quantitative methodology, allowing to answer the research questions of this study. Therefore, results show that, in order to improve Millennial’s retention in the consulting industry in Portugal, managers should comprehend and study the younger individuals within Generation Y and what are the work characteristics that most contribute to their job satisfaction and influence their decision to change jobs since the Younger Group of Millennials represents the future of the workforce. Only then, it will be possible for managers to concentrate on developing efficient human resources practices and policies for future generations.